Paket Intervensi Kesehatan Esensial pada Remaja Putri Sebagai Langkah Memutus Siklus Stunting: Sebuah Tinjauan Literatur: Essential Health Intervention Package for Adolescent Girls as a Step to Break the Stunting Cycle: A Literature Review - Widaryanti, Rahayu; Dana, Yoga Adhi; Istiqomah, Dedeh; Nugraheni, Sri Achadi (Universitas Airlangga, 2024)
Background: In Indonesia, approximately 32% of Indonesian adolescents experience anemia, if it not addressed effectively, adolescents suffering anemia pose a risk of resulting in stunted growth in their future offspring. Addressing nutritional issues including anemia in adolescence is a crucial step in efforts to break the cycle of stunting. Objectives: This study aimed to review and analyze various essential health interventions for adolescent girls as a strategy to break the cycle of stunting through a comprehensive article review. Methods: Literature was collected from four English-language databases: Scopus, PubMed, Springer Link, and EBSCOhost published from January 2013 to November 2023. The authors conducted article searching using the keywords